Cote d'Ivoire : Poverty Reduction Strategy Paper: Executive Summary of Progress Report. (IMF Staff Country Reports; Country Report ;, 2015)
This paper discusses the progress made on Cote d'Ivoire's National Development Plan (PND) 2012-15. In the area of planning, the 2012-13 PND served to move planning to the forefront of public action. In addition, the National Bureau of Population has been set up to better address the problems of population and development. In the area of justice and human rights, the policy guidance paper has been prepared and is now being implemented. In the area of civil protection, the actions carried out have centered on strengthening the institutional and legal framework for preventing and managing risks and disasters and building up the operational capabilities of bodies in charge of civil protection.